Hypertension, Gender, Older Age, and Their Relationships with COVID-19 Mortality: Meta-Analysis - Annissa Devi Permata; Bhisma Murti; Didik Gunawan Tamtomo (Masters Program in Public Health, 2021)
Background: Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCoV-2). SARS-CoV-2 is a new type of coronavirus that has never been previously identified in humans. Globally, 213 countries (as of August 11, 2020) are facing serious consequences from the ongoing COVID-19 pandemic. This study aimed to analyze the magnitude of the relationship of hypertension, gender, and older age to COVID-19 mortality with a meta-analysis study. Subjects and Method: This was a systematic review and meta-analysis conducted by following the PRISMA flow diagram. The article search process is carried out through a journal database which includes: PubMed, Science Direct, Springer Link, and PMC Europe by selecting articles published in 2020-2021. The keywords used included: “sex” OR “gender” AND “older age” AND “hypertension” AND “mortality” OR “death” OR “fatal outcome” OR “Predictors outcome” OR “Impact” AND “coronavirus” OR “Covid-19” OR “SARS-COV-2” OR “2019 n-Cov” OR “severe acute respiratory syndrome related coronavirus”. The inclusion criteria were full text articles with a retrospective cohort study design. The article is in English, and the analysis used is multivariate with adjusted Odds Ratio. Eligible articles were analyzed using the Revman 5.3 app. Results: A total of 20 articles were reviewed in this study. A meta-analysis of 10 retrospective cohort studies showed that hypertension increased COVID-19 mortality by 1.40 times compared with no hypertension (aOR= 1.40; 95% CI= 1.04 to 1.89; p = 0.030). A meta-analysis of 10 retrospective cohort studies showed that males had a 1.42 times increased risk of COVID-19 mortality compared to females (aOR= 1.42; 95% CI= 1.20 to 1.67; p<0.001). Meta-analysis of 7 retrospective cohort studies showed that old age has a 3.42 times increased risk of COVID-19 death compared to younger age (aOR=4.15; 95% CI= 2.35 to 7.32; p <0.001). Conclusion: Hypertension, gender, and old age increase the risk of dying from COVID-19.